Effect of Reduced 𝑘0 Zone on Time-Dependent Analysis of Tunnels - Mohammed Y. Fattah; Kais T. Shlash; Nahla M. Salim (Advances in Civil Engineering)
The problem of the proposed “Baghdad metro line” which consists of two routes of 32 km long and 36 stations is analyzed. The tunnel is circular in cross-section with a 5.9 m outer diameter. The finite element analyses were carried out using elastic-plastic and modified Cam clay models for the soil. The excavation has been used together with transient effects through a fully coupled Biot formulation. All these models and the excavation technique together with Biot consolidation are implemented into finite-element computer program named “Modf-CRISP” developed for the purpose of these analyses. The results indicate that there is an inward movement at the crown and this movement is restricted to four and half tunnel diameters. A limited movement can be noticed at spring line which reaches 0.05% of tunnel diameter, while there is a heave at the region below the invert, which reaches its maximum value of about 0.14% of the diameter and is also restricted to a region extending to 1.5 diameters. The effect of using reduced 𝑘0 zone on excess pore water pressure and surface settlement (vertical and horizontal) was also considered and it was found that the excess pore water pressure increases while the settlement trough becomes deeper and narrower using reduced 𝑘0.